The Opposition of Ethnic Interests As One of the Key Causes of Yugoslav State Disintegration - Instead of the Editorial - Miladinovic, Slobodan M. (Sociološki pregled, 2019)
Yugoslavia was created in 1918 under the name of the Kingdom of Serbs, Croats and Slovenes. Prior to its creation, there were discussions on whether it should be a unitary state of one nation with three tribes or a federation of equal peoples. In the period between the two wars, the state was unitary, becoming a federal republic afer the end of the Second World War. Afer the creation of the common state, there was a continuing conﬂict between individual peoples and their political elites, and there was visible rivalry between Serbs and Croats, in particular, that occasionally escalated into open conﬂicts. Over time, national relations grew increasingly complicated. In the post-war period, research found a high presence of ethnic stereotypes, distances and prejudices. There were multiple attempts to bring them into balance, by means of establishing the Yugoslav nation afer the 6 January Dictatorship, then the community of equal peoples and nationalities, afer the Second World War, forcing the ideology of fraternity and the unity of nations and nationalities, and funally openly advocating the thesis on the disintegration and the creation of independent national states. The fnal disintegration of Yugoslavia can be assessed as a result of ethnic conﬂicts rather than of economic underdevelopment. Keywords: Yugoslavia, national relations, Yugoslavism, ideology, political elite